2019
DOI: 10.5993/ajhb.43.4.16
|View full text |Cite
|
Sign up to set email alerts
|

Drug and Alcohol Abuse: the Role of Economic Insecurity

Abstract: L ife expectancy in the United States (US) rose nearly every year between 1943 and 2014, 1 but between 2014 and 2017 the country experienced the longest sustained decline since 1915-18. 2-5 Much of the decline has been attributed to the drug epidemic. 5-8 Increased availability of opioids resulting from changes in marketing, prescribing, and insurance coverage of prescription opioids, which led to wider black market dissemination of heroin, fentanyl, and other opioids almost certainly contributed to growing dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 39 publications
0
18
1
1
Order By: Relevance
“…Previous studies have reported an association between high residential mobility and the development of alcohol and other drug-related problems among adolescents and young adults (28). We did not find such an association, possibly because high educational attainment and economic security in our study subjects provided protective factors against substance abuse (29).…”
Section: Discussioncontrasting
confidence: 77%
“…Previous studies have reported an association between high residential mobility and the development of alcohol and other drug-related problems among adolescents and young adults (28). We did not find such an association, possibly because high educational attainment and economic security in our study subjects provided protective factors against substance abuse (29).…”
Section: Discussioncontrasting
confidence: 77%
“…Other research discounts the purely economic motivations for opioid abuse. Glei and Weinstein (2019) observe that drug abuse may be related to perceived economic distress that is not captured by headline statistics. Ruhm (2019) finds that drug death rates increased more in places experiencing relative economic decline than in places with more robust economic growth, but he attributes this weak relationship to confounding factors related to the demographic composition of places.…”
Section: Evidence In the Literaturementioning
confidence: 99%
“…Previous studies which empirically tested the relative deprivation hypothesis have been presented the negative impacts of relative deprivation on various health outcomes. These negative effects are manifested in the increased prevalence of chronic diseases ( 17 , 18 ), stress-related health behavior, such as smoking and drug abuse ( 19 , 20 ) and poor self-rated health ( 21 ), functional disability ( 22 ) and mortality ( 23 ). However, the research results diverged, when considering different health outcomes.…”
Section: Introductionmentioning
confidence: 99%